Reconstruction to Prove Elements of Detrimental to State Finances in the Criminal Act of Corruption in Indonesia - Firmansyah Firmansyah; Topo Santoso; Febrian Febrian; Nashriana Nashriana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractState financial loss is one of the elements of the criminal act of corruption in Article 2 paragraph (1) and Article 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption Crime. The formulation of the element of detrimental to state finances in the two articles at the level of evidence still raises various obstacles because it is an obscure norm and is multi-interpretative. The results of the research show that proving that the element of detrimental to state finances in the criminal act of corruption is still understood as a formal crime so that the proof is sufficient by fulfilling the act and there is no need for consequences, whether potential loss of state finances or actual loss, the perpetrator can be convicted. After the Constitutional Court through its decision Number 25/PUU-XIV/2016 stated that the word